2014
DOI: 10.1007/s11255-014-0775-1
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal microvascular endothelial function and the microinflammatory state are associated with baseline peritoneal transport characteristics in uremic patients

Abstract: Uremic patients display differences in peritoneal microvascular endothelial function and microinflammatory states before peritoneal dialysis. Patients of the high transport group have higher MVD, increased expression of endothelial function markers (VEGF and eNOS), and the microinflammatory marker (IL-6). These observations are closely related to high baseline peritoneal transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In the studies using human tissues, we confirmed that there was a correlation between peritoneal transport rate and VEGF-A or TGF-␤1 concentrations in PD effluent, as previously reported (32,38,43,44). Importantly, we found that the VEGF-A concentration in PD effluent correlated with TGF-␤1 concentrations (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In the studies using human tissues, we confirmed that there was a correlation between peritoneal transport rate and VEGF-A or TGF-␤1 concentrations in PD effluent, as previously reported (32,38,43,44). Importantly, we found that the VEGF-A concentration in PD effluent correlated with TGF-␤1 concentrations (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The peritoneal membrane consists of a mesothelial cell monolayer, a submesothelial space composed of extracellular matrix, numerous small blood vessels and few lymphatic vessels and nerves, mostly organized in three distinct layers [ 53 ]. Peritoneal microvessel density correlates with small solute transport rates [ 17 , 54 ]; the vascular endothelium is considered the primary, rate limiting barrier [ 32 , 33 , 34 ]. Alterations in the endothelial barrier characteristics should significantly modify PD clearance functions.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanism of late acquired high transport induced by long-term peritoneal dialysis is different from that of early inherent high transport [ 23 , 24 ]. After initiating PD, significant changes occur in the transport characteristics, which may be due to the differences in the structure and function of the peritoneum before dialysis; these differences mainly manifest as microvascular endothelial function and microinflammation of the peritoneum [ 11 , 25 ]. Genetic factors are involved in determining initial peritoneal status.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization contributes to both initial fast PSTR and fast PSTR in long -term PD. Although more studies have focused on neovascularization in long-term exposure in PD, several studies have shown higher concentrations of VEGF and KDR in peritoneal tissue in PD patients with initial high/high average transport than in patients with low/low average transport, which means that local expression of VEGF and KDR in peritoneal tissue can affect peritoneal baseline transport by increasing the number of new peritoneal vessels and increasing inflammation status [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%